A meta-control algorithm for generating approximate solutions to binary integer programming problems - von Haartman, Kathrine; Kohn, Wolf; Zabinsky, Zelda B. (Nonlinear analysis. Hybrid systems, 2008)
Binary integer program problems, which are known to be difficult to solve, have long been an important research area. We use a new approach with continualization techniques to find approximate solutions to binary integer programming problems. The algorithm constructs a sequence of approximations to a solution using a meta-control approach that has low polynomial time complexity. The algorithm is illustrated with a BIP example.